2021
DOI: 10.1177/00027642211000413
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Crisis on Marginal Migrant Populations in Italy

Abstract: This article analyzes the impact of the COVID-19 pandemic on marginal migrant populations, and the Italian response to cope with the crisis. The first section uses different sources of data to highlight social, political, and economic processes, already present in the pre-emergency stage, that contributed to the exposure of migrants to higher levels of vulnerability. The second part analyzes the impact of the crisis and its management in the response stage, focusing in particular on the perspective of front li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…For example, Italy required documentation to leave the house during lockdown periods, inherently disadvantaging undocumented migrants or migrants working in informal sectors. Initial response efforts in Italy did little to address migrant populations’ social and legal precarities; instead, they focused on one-size-fits-all mandates to mitigate the biomedical aspects of COVID-19 and maintain national power structures [ 22 ]. The limited considerations for social determinants in COVID-19 response policy created a heightened risk of violence for migrant and refugee women, who described increased abuse in institutions and their homes during the lockdown period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Italy required documentation to leave the house during lockdown periods, inherently disadvantaging undocumented migrants or migrants working in informal sectors. Initial response efforts in Italy did little to address migrant populations’ social and legal precarities; instead, they focused on one-size-fits-all mandates to mitigate the biomedical aspects of COVID-19 and maintain national power structures [ 22 ]. The limited considerations for social determinants in COVID-19 response policy created a heightened risk of violence for migrant and refugee women, who described increased abuse in institutions and their homes during the lockdown period.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Italy served as the reception context for over 40% of Europe’s migrant arrivals, many of whom were refugees and asylum seekers [ 21 ]. While conditions in reception centers presented challenges prior to the pandemic, the spread of the virus created new and exacerbated prior health vulnerabilities and access barriers for resident migrants across the country [ 22 ]. For example, a quantitative study found that migrants living in reception centers in northern Italy had a higher incidence of COVID-19 as compared to the Italian resident population [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Where available, assistance and welfare come from NGOs, third sector associations, voluntary groups and informal networks formed by migrants themselves. 19,20,21 However, this is often on an ad hoc basis, and organisations are unevenly spread across the city.…”
Section: Urban Life For Undocumented Migrantsmentioning
confidence: 99%
“…This occurred especially in the productive sectors characterized by a high level of informality and undeclared work, 7 In North America (the United States: Benfer et al, 2021;Despres, 2021;Gonzalez et al, 2020;Luconi, 2021;Olayo-Méndez et al, 2021;Canada: Tuyisenge & Goldenberg, 2021); in South America (Brazil: Brigido et al, 2022;Parise et al, 2021); in Asia (Hiraiwa, 2021;Reddy, 2021); in Southeast Asia and the Indian subcontinent (Singapore: Hayward et al, 2021;Hintermeier et al, 2021;the Philippines: Asis, 2021;Ciceri & Prigol, 2021;India: Acharya & Patel, 2021;Saikia, 2021;Bangladesh: Parvez, 2021); in the Middle East (Saudi Arabia: Hayward et al, 2021;Hintermeier et al, 2021); in Europe (Italy: Della Puppa & Sanò. 2021; Quaranta et al, 2021;Sanfelici, 2021;the Netherlands: Coyer et al, 2021;France: Marin & Pelloquin, 2021;Spain: Rinaldi, 2021;Greece: Kukreja, 2021), in Africa (Ferraro & Chapman, 2021); in Australia (Ricatti, 2021). 8 For the Gulf area see Abella & Sasikumar, 2020. which see a strong presence of immigrants such as domestic work (Rinaldi, 2021).…”
Section: The Impact On Migrant Workers and Families: Health Work And ...mentioning
confidence: 99%